The Urgency of Transforming Indigenous Knowledge into Contextual Science Practicum Activities: A Preliminary Study among Preservice Science Teachers and Science Educators - Ahmad Aris Arifin; Agus Ramdani; A. Wahab Jufri; Satutik Rahayu (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This preliminary study aimed to examine the need for validated instructional support in transforming Sasambo indigenous knowledge into contextual science practicum activities for preservice and in-service science teachers. A descriptive survey design was employed involving 100 respondents, consisting of 76 preservice science teachers from Biology, Physics, and Chemistry Education programs and 24 in-service science teachers. These groups were selected to obtain complementary perspectives: preservice teachers represent future science educators who require contextual pedagogical preparation, whereas in-service teachers provide practical insights from classroom practice. Data were collected using an online questionnaire comprising nine closed-ended items related to the availability of science learning resources, the integration of Sasambo local wisdom into science learning, and the need for validated instructional support. The questionnaire was reviewed by experts to ensure content validity and tested for internal consistency to confirm instrument reliability. Descriptive statistics, including frequencies and percentages, were used to analyze the data. The findings revealed substantial gaps in current science learning support. Most respondents perceived science learning resources and portals as limited (82%), reported difficulty finding complete instructional materials (83%), and experienced challenges in accessing reliable and expert-validated resources (87%). The integration of Sasambo local wisdom into science learning was also limited, as 81% of respondents had never connected Sasambo local wisdom with science learning, 82% had difficulty integrating it into science content, and 87% had never implemented Sasambo-based ethno-practicum activities. In contrast, respondents expressed strong support for the development of an integrated learning platform: 98% indicated the need for a portal providing complete and validated instructional materials, 93% agreed that a Sasambo ethno-practicum portal would support innovative learning design, and 96% emphasized the need for reconstructed ethno-Sasambo data. These findings highlight the urgent need to develop validated, contextual, and accessible ethno-practicum learning support to facilitate the transformation of indigenous knowledge into meaningful science practicum activities.